2021
DOI: 10.1038/s41419-021-04159-9
|View full text |Cite|
|
Sign up to set email alerts
|

A novel function of NLRP3 independent of inflammasome as a key transcription factor of IL-33 in epithelial cells of atopic dermatitis

Abstract: Atopic dermatitis (AD) is a common chronic pruritic inflammatory skin disorder characterized by recurrent eczematous lesions. Interleukin (IL)−33, a cytokine of the IL-1 family, was found to play an important role in the pathogenesis of AD. As a key component of the inflammasome, NLRP3 has been mostly described in myeloid cells that to mediate inflammasome activation conducted proinflammatory cytokine production of the IL-1 family. However, the role of NLRP3 inflammasome in the pathogenesis of AD, as well as I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 54 publications
0
33
0
2
Order By: Relevance
“…Indeed, we observed that cervical dilation and decidual inflammation were both tempered in Nlrp3 -deficient mice independently of CASP-1 activation and maturation of IL-1β, and the baseline expression of cervical tissue genes was different between WT and KO mice. Consistently, the NLRP3 molecule has been previously reported as exhibiting inflammasome-independent functions that include tissue repair ( 96 ), Th2 cell differentiation ( 97 ), restriction of protective early neutrophil responses ( 98 ), and activity as a transcription factor ( 99 ); therefore, it is plausible that such NLRP3-mediated, inflammasome-independent processes could be participating in cervical dilation and decidual inflammation. Moreover, this may also explain why Nlrp3- deficient mice seemed to have low concentrations of total IL-1β in the cervical and decidual tissues upon LPS administration.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, we observed that cervical dilation and decidual inflammation were both tempered in Nlrp3 -deficient mice independently of CASP-1 activation and maturation of IL-1β, and the baseline expression of cervical tissue genes was different between WT and KO mice. Consistently, the NLRP3 molecule has been previously reported as exhibiting inflammasome-independent functions that include tissue repair ( 96 ), Th2 cell differentiation ( 97 ), restriction of protective early neutrophil responses ( 98 ), and activity as a transcription factor ( 99 ); therefore, it is plausible that such NLRP3-mediated, inflammasome-independent processes could be participating in cervical dilation and decidual inflammation. Moreover, this may also explain why Nlrp3- deficient mice seemed to have low concentrations of total IL-1β in the cervical and decidual tissues upon LPS administration.…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown that the upregulation of NLRP3 inflammasome is associated with the pathogenesis of chronic dermatitis in the skin of mice [ 37 ]. To determine whether the symptoms of AD were attenuated via the inhibition of the NLRP3 inflammasome, we investigated whether the application of M. concanensis inhibited the NLRP3 inflammasome in DNCB-induced lesional ear tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it is increasingly recognized that members of the intracellular sensor protein NLR family act independently of inflammasomes. 223 , 224 Janowski et al found that NLRC4 in TAMs inhibits melanoma progression by enhancing T cells function. When NLRC4 is defective in mice, macrophages are less able to produce cytokines and chemokines, and subsequently less able to recruit T cells near the tumor, which promotes tumor growth, independent of the inflammasome components ASC and CASP1.…”
Section: Pyroptosis Synergizes Antitumor Immune Responsementioning
confidence: 99%